PENGEMBANGAN BAHAN AJAR BERMUATAN LITERASI BERBASIS FIGMA PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV SD NEGERI 104205 TEMBUNG - Puspasari, Maharani; Halimatussakdiah; Wildansyah Lubis; Edizal Hatmi; Masta Marselina Sembiring (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a product intended for use in the educational process and to evaluate the feasibility, practicality, and effectiveness of Figma-Based Literacy Teaching Materials in the Indonesian Language curriculum for fourth grade students at SD Negeri 104205 Tembung. The research employs a Research and Development (R&D) methodology, utilizing the ADDIE model, which encompasses five distinct phases: analysis, design, development, implementation, and evaluation. The subjects of this research are fourth-grade students utilizing the Figma-Based Literacy Teaching Materials within the Indonesian Language subject. Data collection instruments include observation, interviews, material validation questionnaires, media design validation questionnaires, educational practicality questionnaires, and assessment tests. The findings from the development of the Figma-based literacy teaching materials for the Indonesian Language subject indicate that the material validation received a percentage score of 88%, categorizing it as "Very Valid." Additionally, the validation conducted by media design experts yielded a score of 90.5%, also classified as "Very Valid," thereby confirming that the media is suitable for implementation in the educational process. In terms of practicality, feedback obtained from teachers through questionnaires resulted in a percentage score of 95%, categorized as "Very Practical." Effectiveness assessments, conducted via pretests and posttests, demonstrated an average N-gain of 66.9%, which is classified within the "effective" range.